Pengaruh Penundaan Waktu Prosesing Terhadap Mutu Benih Padi (Oryza sativa l.) Varietas Membramo - NUNO, LUCIO; RAKA, I GUSTI NGURAH; YUSWANTI, HESTIN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2017)
The Influence of Processing Time Delay To Rice (Oryza Sativa L.) Seed Quality of Membramo Variety This research was performed with the purpose to obtain tolerance of processing time delay after appropriate crop so it doesn’t affect the physical and physiological quality of rice (Oryza Sativa L.) seed. This experiment used the Complete Random Design (RAL) by using 8 treatments and 3 repetitions. Therefore, there are 24 experiment units. Research result data were tabulated and analyzed mode investigation according to design that was used, and if the treatment has significant influence then it is proceeded with Duncan’s multiple distance test (5%). Observation was carried out to water content variable during the crop (%), water content during the processing (%), water content during the test (%), the viability test/power of germination (%) and electrical conduction power test (? mhos cm-2 g1). Research results shows that the longer processing time delay the more increase clear water content, the lowest water content at the direct harvest processing and the highest at processing time delay at the seventh day. So thus the longer processing time delay the viability processing will decrease. The processing time delay until 2 days after the crop the rice seed viability is more than 80% (above quality standard, ISTA), the next delay the seed viability is already under standard. The electrical conduction power more increase by the longer seed processing time delay.